2015
DOI: 10.11604/pamj.2015.20.334.6052
|View full text |Cite
|
Sign up to set email alerts
|

Human resource capacity for information management in selected public healthcare facilities in Meru County, Kenya

Abstract: IntroductionReliable health information is essential for decision making in the healthcare system. Information management in Kenya was considered the weakest area under the Health Information System pillar mainly due to inadequate health workers capacity. The study therefore aimed at assessing health workers skills and current training needs for information management in the selected healthcare facilities.MethodsCross-section research design was adopted and both purposive sampling technique and censuses were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…The study revealed that the majority were not able to perform such tasks: only 17% of the 121 health professionals could check for data accuracy, compute trends from bar charts or convert the collected data into meaningful information for use. This discovery is consistent with their finding that 91% had never received training for information management [20]. These figures show no progress compared to earlier evidence from a 15-country study: 13 out of 21 LMIC sites studied included personnel trained in data management or data quality control [28].…”
Section: Data Management Skills and Analysis Skillssupporting
confidence: 88%
See 3 more Smart Citations
“…The study revealed that the majority were not able to perform such tasks: only 17% of the 121 health professionals could check for data accuracy, compute trends from bar charts or convert the collected data into meaningful information for use. This discovery is consistent with their finding that 91% had never received training for information management [20]. These figures show no progress compared to earlier evidence from a 15-country study: 13 out of 21 LMIC sites studied included personnel trained in data management or data quality control [28].…”
Section: Data Management Skills and Analysis Skillssupporting
confidence: 88%
“…In northwest Ethiopia, 356 (59%) of the 606 health professionals studied were computer literate [10]. A smaller-scale assessment in Kenya found that approximately half (58 out of 121) of the health workers had no knowledge on how to use computers, which contributes to further limitations in data analysis and utilization skills [20]. Studies in Iran [21], Nigeria [13] and India [22] have found variation in nurses' computer skills, the Iranian study reporting the mean of 43% of computer skills based on the International Computer Driving License (ICDL) [21].…”
Section: Computer Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…A data collector collects or supplies data for the PHIS. Of the 45 articles, 23 assessed the performance of data collectors 14,[29][30][31]33,35,[38][39][40]44,46,47,49,51,55,57,59,60,62,66,[68][69][70] (see Table 1). Details of facilitators and barriers for data collector are shown in Supplemental Appendix Table 2. A data collector is a stakeholder with whom the data user should build up and nurture a relationship.…”
Section: Data Collectormentioning
confidence: 99%